A systems study on Montealba Mix & Concrete Product Incorporation - Lim, Beatrice Anne G.; Pabua, Maria Angela T.; Suarez, Jessa Rica N.
Montealba Mix & Concrete Product Corporation's Concrete Hollow Block (CHB) production plant is currently experiencing problems with overstocking 4" and 5" CHBs by 334% and 29.4% respectively, while understocking 6" CHBs by 2%, against target safety stocks. This causes about 10% of the orders of their walk-in customers to end up as missed sales, resulting into an unrealized profit amounting to -Php 66,451 in roughly 5 months or -Php 13,290.2 per month. In order to solve this, multiple alternatives were generated, evaluated, and shortlisted, until only three of these were left. These alternatives are Setting Production Targets, Revising Inventory Tracking Methods, and Inventory Management for Cement. Data points from February 28 to March 30, 2019 were gathered and used for simulation to know what would happen if the company were able to adapt the proposed system, and to validate whether or not the alternatives had addressed the problem. For the Setting of Production Targets alternative, the group compared the Mean Absolute Deviation (MAD) values of the previous system and that of the proposed one, against the actual demand data. The proposed forecasting method consistently has a lower MAD value compared to that of their actual production data. This translates to an improvement of 55.41%, 45.73%, and 37.72% for the 4-inch, 5-inch, and 6-inch CHBs respectively. It was also found that given the company's current demand and production processes, they should be able to reach the forecasted production targets. Implementing this does not disrupt the current production processes as it only affects production planning, and all simulated production target values, based from historical data, can be accommodated by the current system as exhibited. As for Revising Inventory Methods, the results of the simulated data generally shows a more uniform way of inventory level management across all the CHB sizes as compared to their inconsistent output, sales and inventory tracking. Although this alternative does not directly contribute in addressing the problem posed, it mostly serves to reinforce the Setting of Production Targets alternative by providing more accurate data to be used for it. The Inventory Management for Cement alternative also supports the first alternative, as its improvements on the system is tied to that of the improvements from setting production targets. Its implementation would ensure that the company would have enough cement to produce the necessary targets and attain the percentages of improvement brought about by the first alternative. Overall, it was found that the overstocking of sizes 4"and 5"CHBs decreased compared to the company's actual values, and the understocking of size 6" CHB was eliminated, reducing missed sales from a historical value of -Php 13, 290.20 per month to only Php 335.